JIWA WIRAUSAHA ADALAH PEMBURU KESUKSESAN - R Gatot Heru Pranjoto (Eco-Entrepreneur, 2016)
Competition in the global market was won by the failure of entrepreneurs to use your skills, experience, education, creativity and the ability innovative to capture business opportunities in accordance with the wishes and expectations of consumers, then transform that information into a company's operations to produce products that have added value, quality at low prices , according to market demand and competition.